Implementation of Pesantren Curriculum Updates as an Effort to Improve Life Skills and Entrepreneurial Knowledge - Febryan Hadinata; A Andari; MA Ansori; Purwanti Purwanti (International Journal Labs, 2023)
Pesantren is an Islamic educational institution that has an important role in the development of Indonesian society. Pesantren has been part of the culture and tradition of Indonesian society for centuries. This study aims to examine the implementation of pesantren curriculum renewal as an effort to improve the life skills and entrepreneurial knowledge of pesantren graduates. This research uses qualitative research methods. The data collection technique in this research is a literature study obtained from Google Scholar. The data that has been collected is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the direction of updating the pesantren curriculum had a positive impact on improving the life skills and entrepreneurial interests of pesantren graduates. This can be seen from the increasing ability of pesantren graduates in terms of the ability to think critically and solve problems, the ability to communicate and collaborate, the ability to adapt to change, and entrepreneurial interest. The renewal of pesantren has implications including improving the quality of education in pesantren, increasing the competitiveness of pesantren, and increasing the role of pesantren in society. However, pesantren renewal must be done carefully so as not to eliminate the basic values of pesantren.